Metal ion doped hard carbon material as well as preparation method and application thereof

Through the dual-effect synergistic preparation method of metal ion doping and molten salt, the problems of low capacity and poor electrochemical stability of hard carbon materials in sodium ion batteries are solved, and hard carbon with high capacity, excellent electrochemical performance and environmentally friendly preparation are achieved Material.

CN119447229APending Publication Date: 2025-02-14BEIJING INST OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411485377.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Hard carbon materials have low capacity in sodium ion batteries, low Coulomb efficiency in the first week, poor electrochemical stability, and short reversible cycle life.

Method used

The metal ion doping and molten salt are used to prepare the dual-effect synergistic method. By mixing the metal ion salt, molten salt, carbon source and reaction solvent, and freeze-drying, heat treatment is carried out to obtain a metal ion doped hard carbon material.

Benefits of technology

The electrochemical properties of hard carbon materials are improved, their capacity in sodium ion batteries, first-week Coulomb efficiency and reversible cycle life are enhanced, while reducing environmental pollution caused by template methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447229A_ABST
    Figure CN119447229A_ABST
Patent Text Reader

Abstract

The invention relates to a metal ion doped hard carbon material and a preparation method and application thereof, and belongs to the technical field of secondary battery electrode materials. And uniformly mixing the metal ions, soluble molten salt and a carbon source, performing freeze-drying treatment, performing heat treatment on an obtained reaction product in an inert atmosphere, and removing residual molten salt by washing to obtain the porous metal ion-containing electrode material. The electrode material prepared according to the invention has excellent electrochemical performance, the carbon material can be well suitable for a sodium ion battery, and heteroatom doping provides more active sites for sodium ions, so that the reversible capacity of the hard carbon material can be further improved; metal ions provide active sites, promote local graphitization of the hard carbon material, inhibit excessive graphitization of the material and improve the reversible cycle capacity of the material. According to the carbon material prepared by the method, environmental pollution caused by a template method is reduced, and meanwhile, the electrochemical performance of the hard carbon material is improved to a great extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a metal ion-doped hard carbon material and a preparation method and application thereof, belonging to the technical field of secondary battery electrode materials. Background Art

[0002] Sodium-ion batteries have the advantages of abundant raw materials, low prices, and wide distribution, which can solve the problems of lithium resource shortage and high cost faced by lithium-ion batteries. With the continuous development, the energy density, cycle life and safety of sodium-ion batteries have been significantly improved, and they have gradually become a potential alternative for energy storage systems and electric vehicles.

[0003] The existing negative electrode materials for sodium ion batteries include: carbon-based, titanium-based, organic, alloy and other negative electrode materials. Among them, carbon-based materials are the negative electrode materials with the most commercial prospects. As a kind of carbon-based material, hard carbon has the advantages of low cost, environmental friendliness and wide sources compared with other negative electrode materials for making negative electrodes for sodium ion secondary batteries. Therefore, hard carbon is currently one of the most promising negative electrode materials for sodium ion batteries. However, if hard carbon materials are to be used as negative electrodes for sodium ion batteries, the following problems need to be solved: the capacity of hard carbon materials is low, the coulomb efficiency in the first week is low, the electrochemical stability is poor, and the reversible cycle life is short.

[0004] In order to solve the problem of low capacity of hard carbon materials, the pore-forming method is usually used to increase the specific surface area to improve the adsorption capacity and to regulate the hard carbon structure to form local graphite domains to increase the embedding capacity. When using the pore-forming method, after the pore-forming agent completes the pore-forming effect, it is necessary to use hazardous chemicals such as hydrochloric acid or hydrofluoric acid to remove the pore-forming template. Therefore, the preparation process is more complicated and has many defects such as high cost and environmental pollution. Summary of the invention

[0005] The technical problem solved by the present invention is: to overcome the deficiencies of the prior art and to provide a metal ion-doped hard carbon material and a preparation method and application thereof.

[0006] The technical solution of the present invention is:

[0007] A metal ion doped hard carbon material is porous carbon in which metal ion single atoms are dispersed, and the carbon material has excellent electrochemical properties.

[0008] A method for preparing a metal ion-doped hard carbon material, the raw materials used in the method include metal ion salt, molten salt, carbon source, and reaction solvent; the steps of the method include:

[0009] In the first step, the metal ion salt, the molten salt, the carbon source and the reaction solvent are mixed and stirred to obtain a colloidal mixture;

[0010] In the second step, the colloidal mixture obtained in the first step is freeze-dried to obtain a precursor;

[0011] The third step is to heat-treat the precursor obtained in the second step, and then wash it with water to obtain a metal ion-doped hard carbon material;

[0012] The metal ion salt is at least one of ferric acetate, ferric chloride, ferric sulfate, ferric nitrate, nickel acetate, zinc acetate, tin acetate, manganese acetate, copper acetate, and cobalt acetate;

[0013] The molten salt is sodium chloride or potassium chloride;

[0014] The carbon source is at least one of chitosan, chitin, fructose, xylose, glucose and cellulose;

[0015] The reaction solvent is an acetic acid aqueous solution, and the mass concentration of the acetic acid aqueous solution is 0.1%-2%;

[0016] In the first step, the mixing temperature is room temperature, the stirring speed is 600-1200 r / min, and the stirring time is 8-14 h; preferably, the stirring speed is 700-900 r / min, most preferably 800 r / min, and the most preferred time is 12 h;

[0017] Assume the amount of metal ion salt added is a;

[0018] Then the ratio of the amount of metal ion salt added, the mass of molten salt, the mass of carbon source and the volume of reaction solvent is a: 2g: 2g: 71mL;

[0019] The calculation method of a is: a = the mass fraction of metal element added to the solid raw material, that is,

[0020] a = metal ion mass / (metal ion salt mass + carbon source mass + molten salt mass)

[0021] The value range of a is 0.5%-5%;

[0022] In the second step, freeze drying conditions are freeze drying at -60°C to -50°C for 10-14h;

[0023] In the third step, the heat treatment temperature is 800-1600°C, and the heat treatment time is 1-3h; preferably 1100-1300°C, and most preferably 1200°C. The heating rate during the heat treatment is preferably 1-5°C / min, and most preferably 3°C / min.

[0024] An application of a metal ion-doped hard carbon material, wherein the obtained metal ion-doped hard carbon material is prepared into a slurry, then coated on the surface of a metal substrate and dried to obtain a negative electrode material, and the obtained negative electrode material is used as a negative electrode of a secondary sodium ion battery in the secondary sodium ion battery, and the obtained secondary sodium ion battery has high capacity and good rate performance, and the metal substrate is copper foil or aluminum foil; the drying temperature is 80-120° C., and the drying time is 12-24 hours;

[0025] The method for preparing the slurry is: mixing the metal ion-doped hard carbon material, carbon black (super P) and carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1.

[0026] Beneficial Effects

[0027] The invention relates to a metal ion-doped hard carbon material and a preparation method and application thereof, belonging to the technical field of secondary battery electrode materials.

[0028] The present invention relates to a preparation method and application of a metal ion-doped high-capacity hard carbon material. The high-capacity carbon material is prepared by the dual-effect synergistic combination of metal ion doping and molten salt. The preparation method is as follows: the metal ions, soluble molten salt and carbon source are evenly mixed and then freeze-dried. The obtained reaction product is heat-treated in an inert atmosphere and then washed with water to remove the residual molten salt to obtain a porous metal ion-containing electrode material. The electrode material prepared according to the present invention has extremely excellent electrochemical properties. The carbon material can be well applied to sodium ion batteries. Heterogeneous atom doping provides more active sites for sodium ions, which can further improve the reversible capacity of the hard carbon material. In addition to providing active sites, metal ions can promote local graphitization of hard carbon materials while inhibiting excessive graphitization of materials, thereby improving the reversible cycle capacity of the material. The carbon material prepared according to this method not only reduces the environmental pollution caused by the template method, but also greatly improves the electrochemical properties of the hard carbon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Sodium charge-discharge performance diagram of carbon material F1 obtained by the dual-effect synergy of metal ion doping and molten salt prepared in Example 1 of the present invention;

[0030] Figure 2 High-resolution transmission electron microscopy image of carbon material F1 obtained by the dual-effect synergy of metal ion doping and molten salt prepared in Example 1 of the present invention;

[0031] Figure 3 A schematic diagram of a process for the controllable preparation of metal ion-doped high-performance hard carbon with local graphitization provided in an embodiment of the present application. DETAILED DESCRIPTION

[0032] The present invention will be described in detail below in conjunction with the embodiments, comparative examples and accompanying drawings. It should be understood that these contents are only used to illustrate and explain rather than to limit the present invention.

[0033] In the following examples / comparative examples, a LANDCT2001A tester (Wuhan Landian Electronics Co., Ltd.) was used to test the charge, discharge and cycle performance of the sodium ion half-cell.

[0034] Example 1

[0035] A metal ion doped hard carbon material, which is porous carbon with metal ion monoatomic dispersion, has excellent electrochemical properties.

[0036] A method for preparing a metal ion-doped hard carbon material, the method comprising the steps of:

[0037] S301, dissolving chitosan, ferric nitrate and sodium chloride in a solution of 70 ml of deionized water and 1 ml of acetic acid, stirring at 800 r / min for 12 h to obtain a colloidal mixture;

[0038] Among them, chitosan is 2g, sodium chloride is 2g;

[0039] The amount of ferric nitrate added is a=2%, and the calculation method is:

[0040] a = the mass fraction of iron added to the solid raw material, that is

[0041] a = added iron mass / (added ferric nitrate mass + chitosan + sodium chloride)

[0042] S302, freeze-drying the colloidal mixture obtained in the first step at -60°C for 12 hours to obtain a precursor;

[0043] S303, heat-treating the precursor obtained in the second step at 1200°C for 2h with a heating rate of 3°C / min, and naturally cooling to room temperature at the end. After the heat treatment, washing is performed to obtain a metal ion doped and molten salt dual-effect synergistic carbon material F1.

[0044] Example 2-5

[0045] S301: dissolving 1%, 3%, and 4% ferric nitrate (the mass fraction of the iron element added to the solid raw material is calculated by the formula: [(mass of iron ions) / (mass of added ferric nitrate + 2g of carbon source + 2g of molten salt)] = 1%, 3%, and 4%) into an aqueous solution containing chitosan and acetic acid and stirring at 800 r / min for 12 h;

[0046] Among them, chitosan 2g, sodium chloride 2g, deionized water 70ml, acetic acid 1ml;

[0047] S302, placing the stirred colloidal precursor in a refrigerator and freezing it for 12 hours, and placing the frozen sample in a freeze dryer until it is completely dry;

[0048] S303, heat-treating the precursor prepared by the above scheme at 1200°C for 2h in an argon atmosphere at a heating rate of 3°C / min, cooling naturally to room temperature at the end, and washing with water to completely remove the soluble molten salt to obtain metal ion-doped carbon materials, which are respectively recorded as F2, F3, and F4.

[0049] Comparative Examples 1-7

[0050] S301, respectively dissolving iron acetate, nickel acetate, zinc acetate, tin acetate, manganese acetate, copper acetate and cobalt acetate into an aqueous solution containing chitosan and acetic acid and stirring at 800 r / min for 12 h;

[0051] The chitosan is 2g, the addition amount of iron acetate, nickel acetate, zinc acetate, tin acetate, manganese acetate, copper acetate and cobalt acetate is 2% (the mass fraction of the metal element added is 2%), deionized water is 70ml, and acetic acid is 1ml;

[0052] S302, placing the stirred colloidal precursor in a refrigerator and freezing it for 12 hours, and placing the frozen sample in a freeze dryer until it is completely dry;

[0053] S303, subjecting the precursor prepared by the above scheme to high temperature heat treatment at 1200°C for 2h in an argon atmosphere at a heating rate of 3°C / min, and naturally cooling to room temperature at the end, to obtain carbon materials doped with different metal ions, which are respectively recorded as D1, D2, D3, D4, D5, D6, and D7.

[0054] Comparative Examples 8-10

[0055] S301, dissolving ferric chloride, ferric sulfate and ferric nitrate in an aqueous solution containing chitosan and acetic acid respectively and stirring at 800 r / min for 12 h;

[0056] Among them, chitosan 2g, ferric chloride, ferric sulfate, ferric nitrate added in an amount of 2% (metal element added mass fraction is 2%), deionized water 70ml, acetic acid 1ml;

[0057] S302, placing the stirred colloidal precursor in a refrigerator and freezing it for 12 hours, and placing the frozen sample in a freeze dryer until it is completely dry;

[0058] S303, the precursor prepared by the above scheme is subjected to high temperature heat treatment at 1200°C for 2 hours in an argon atmosphere at a heating rate of 3°C / min, and is naturally cooled to room temperature at the end, thereby obtaining carbon materials doped with different anions of iron ions, which are respectively recorded as D8, D9, and D10.

[0059] Comparative Examples 11-12

[0060] S301: Sodium chloride and potassium chloride are dissolved in the aqueous solution containing chitosan and acetic acid, respectively, and stirred at 800 r / min for 12 h;

[0061] Wherein: 2g chitosan, 2g sodium chloride, 2g potassium chloride, 70ml deionized water, 1ml acetic acid;

[0062] S302: putting the stirred colloidal precursor into a refrigerator and freezing it for 12 hours, and putting the frozen sample into a freeze dryer until it is completely dried;

[0063] S303: The precursor prepared by the above scheme is heat treated at 1200°C for 2h in an argon atmosphere at a heating rate of 3°C / min. When the temperature is reached, the precursor is naturally cooled to room temperature and then washed with water to obtain soluble molten salt pore-forming carbon materials, which are respectively recorded as D11 and D12.

[0064] Preparation of battery electrodes

[0065] (A) The carbon materials F1, superP and CMC obtained by the dual-effect synergy of metal ion doping and molten salt were weighed in a ratio of 8:1:1, ground evenly, and an equal amount of carboxymethyl cellulose (CMC) as Super P was added, and the mixture was continuously ground into a viscous slurry, which was evenly coated on the copper foil with a scraper.

[0066] (B) The copper foil coated with the carbon material obtained by the dual-effect synergy of metal ion doping and molten salt is placed in an oven for drying and cut into pieces to obtain a battery electrode.

[0067] Electrochemical performance test: Figure 1 The charge and discharge process of the electrode made from F1 in a sodium ion half-cell at a current density of 50 mA / g. Figure 1 It can be seen that the material has extremely excellent charge and discharge reversible capacity and ultra-high first-cycle coulombic efficiency.

[0068] Figure 2 The microscopic morphology of F1 shows that the soluble molten salt plays a role in surface pore formation when subjected to high temperature, and at the same time cooperates with metal ions to regulate the atomic distribution of the material, thereby increasing its degree of graphitization.

[0069] Figure 3 The invention relates to a method and process for preparing a high-capacity hard carbon material doped with metal ions.

[0070] It can be seen that the carbon material obtained by the dual-effect synergy of metal ion doping and molten salt prepared according to the present invention has excellent electrochemical properties, is suitable for use as a hard carbon negative electrode material for sodium ion batteries, and plays a very positive role in the commercial application of sodium ion batteries.

[0071] Table 1: Charging capacity values ​​of each sample in sodium ion half-cell

[0072]

[0073]

[0074] It can be seen from Table 1 that the introduction of only metal ions or soluble molten salts does not significantly improve the reversible cycle capacity of the electrode material. When metal ions and soluble molten salts are introduced at the same time, the electrochemical performance of the material is significantly improved.

[0075] In summary, the carbon materials involved in this patent have relatively excellent electrochemical properties mainly because the addition of metal ions and molten salts regulates the structure of the carbon materials and significantly improves their electrochemical properties. The metal ions and molten salts both affect the degree of graphitization of the materials, catalyzing the appearance of local graphitized structures in the hard carbon materials. At the same time, the amount of addition is regulated to control the degree of graphitization so that the amount added achieves the optimal effect.

[0076] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A metal ion doped hard carbon material, characterized in that: The raw materials of the metal ion-doped hard carbon material include metal ion salt, molten salt, carbon source and reaction solvent; Assume the amount of metal ion salt added is a; Then the ratio of the amount of metal ion salt added, the mass of molten salt, the mass of carbon source and the volume of reaction solvent is a: 2 g: 2 g: 71 mL; The calculation method of a is: a = the mass fraction of metal element added to the solid raw material, that is, a = metal ion mass / (metal ion salt mass + carbon source mass + molten salt mass) The value range of a is 0.5%-5%.

2. The metal ion-doped hard carbon material according to claim 1, characterized in that: The metal ion salt is at least one of ferric acetate, ferric chloride, ferric sulfate, ferric nitrate, nickel acetate, zinc acetate, tin acetate, manganese acetate, copper acetate and cobalt acetate.

3. The metal ion-doped hard carbon material according to claim 1, characterized in that: The molten salt is sodium chloride or potassium chloride.

4. The metal ion-doped hard carbon material according to claim 1, characterized in that: The carbon source is at least one of chitosan, chitin, fructose, xylose, glucose and cellulose.

5. The metal ion-doped hard carbon material according to claim 1, characterized in that: The reaction solvent is an acetic acid aqueous solution, and the mass concentration of the acetic acid aqueous solution is 0.1%-2%.

6. A method for preparing a metal ion-doped hard carbon material, characterized in that the steps include: In the first step, the metal ion salt, the molten salt, the carbon source and the reaction solvent are mixed and stirred to obtain a colloidal mixture; In the second step, the colloidal mixture obtained in the first step is freeze-dried to obtain a precursor; In the third step, the precursor obtained in the second step is subjected to heat treatment, and then washed with water to obtain a metal ion-doped hard carbon material.

7. The method for preparing a metal ion-doped hard carbon material according to claim 6, characterized in that: In the first step, the mixing temperature is room temperature, the stirring speed is 600-1200 r / min, and the stirring time is 8-14 h.

8. The method for preparing a metal ion-doped hard carbon material according to claim 6, characterized in that: In the second step, the freeze-drying condition is freeze-drying at -60°C to -50°C for 10-14h.

9. The method for preparing a metal ion-doped hard carbon material according to claim 6, characterized in that: In the third step, the heat treatment temperature is 800-1600° C., the heat treatment time is 1-3 hours, and the heating rate during the heat treatment is 1-5° C. / min.

10. An application of a metal ion-doped hard carbon material, characterized in that: The obtained metal ion-doped hard carbon material is prepared into a slurry, which is then coated on the surface of a metal substrate and dried to obtain a negative electrode material. The obtained negative electrode material is used as a negative electrode of a secondary sodium ion battery in a secondary sodium ion battery, and the metal substrate is copper foil or aluminum foil; the drying temperature is 80-120°C, and the drying time is 12-24h; the method for preparing the slurry is: the metal ion-doped hard carbon material, carbon black and carboxymethyl cellulose are mixed in a mass ratio of 8:1:1.

Citation Information

Patent Citations

  • Negative electrode material, preparation method thereof and sodium ion battery containing negative electrode material

    CN110407193A

  • Preparation method of high-rate and low-temperature-resistant hard carbon negative electrode material and application of high-rate and low-temperature-resistant hard carbon negative electrode material in sodium-ion battery

    CN116161643A

  • Metal ion modified biomass hard carbon material as well as preparation method and application thereof

    CN117894967A

  • Metal-nonmetal co-doped hard carbon negative electrode material and preparation method thereof

    CN118255343A

  • Preparation method for sodium ion battery porous hard carbon material, and product and use thereof

    WO2024000885A1